DUSP5 functions as a feedback regulator of TNFα-induced ERK1/2 dephosphorylation and inflammatory gene expression in adipocytes - Justine S. Habibian (Nature Portfolio, 2017)
Abstract Adipose tissue inflammation is a central pathological element that regulates obesity-mediated insulin resistance and type II diabetes. Evidence demonstrates that extracellular signal-regulated kinase (ERK 1/2) activation (i.e. phosphorylation) links tumor necrosis factor α (TNFα) to pro-inflammatory gene expression in the nucleus. Dual specificity phosphatases (DUSPs) inactivate ERK 1/2 through dephosphorylation and can thus inhibit inflammatory gene expression. We report that DUSP5, an ERK1/2 phosphatase, was induced in epididymal white adipose tissue (WAT) in response to diet-induced obesity. Moreover, DUSP5 mRNA expression increased during obesity development concomitant to increases in TNFα expression. Consistent with in vivo findings, DUSP5 mRNA expression increased in adipocytes in response to TNFα, parallel with ERK1/2 dephosphorylation. Genetic loss of DUSP5 exacerbated TNFα-mediated ERK 1/2 signaling in 3T3-L1 adipocytes and in adipose tissue of mice. Furthermore, inhibition of ERK 1/2 and c-Jun N terminal kinase (JNK) signaling attenuated TNFα-induced DUSP5 expression. These data suggest that DUSP5 functions in the feedback inhibition of ERK1/2 signaling in response to TNFα, which resulted in increased inflammatory gene expression. Thus, DUSP5 potentially acts as an endogenous regulator of adipose tissue inflammation; although its role in obesity-mediated inflammation and insulin signaling remains unclear.